Neural crest-associated gene FOXD1 induces an immunosuppressive microenvironment by regulating myeloid-derived suppressor cells in melanoma - Sun, Qian; Wang, Nina; Poelchen, Juliane; Peter, Mareike; Novak, Daniel; Özbay Kurt, Feyza Gül; Bitsch, Rebekka; Wu, Huizi; Wang, Yiman; Pardo, Sandra; Han, Rui; Liu, Shibo; et al. (Journal for ImmunoTherapy of Cancer, 2025)
Background Neural crest-associated genes play pivotal roles in tumor initiation, progression, and the intricate dynamics of the tumor microenvironment (TME). Myeloid-derived suppressor cells (MDSC) within the TME are important in dampening T cell activity and contributing to resistance against immunotherapeutic interventions. The neural crest-associated gene Forkhead Box D1 (FOXD1) has been identified as an oncogenic factor that induces melanoma dedifferentiation and progression. However, the underlying mechanisms and the impact of FOXD1 on the antitumor immune response remain unclear.Methods To investigate the impacts of FOXD1 on the melanoma microenvironment, we analyzed publicly available datasets from multiple platforms, including TNMplot, TIMER2.0, etc. In addition, FOXD1 was overexpressed (OE) or knocked down in melanoma cells to identify its biological functions in vitro and in vivo. Flow cytometry and arginase activity assay were used to analyze the phenotype and function of MDSC. Western blot, reverse transcription-PCR, or ELISA assays were employed to analyze the expression of FOXD1 and its downstream effectors. In vivo experiments were conducted to investigate the role of FOXD1 in melanoma progression and the influence on MDSC accumulation within the TME.Results We demonstrate that increased FOXD1 levels inversely correlated with melanoma responsiveness to immunotherapy. Ex-vivo analyses unveiled that monocytes, exposed to conditioned medium from FOXD1-OE melanoma cells, effectively suppressed T cell proliferation and upregulated the expression of programmed death-ligand 1 (PD-L1) and other immunosuppressive factors. FOXD1 was identified as a direct regulator of interleukin 6 (IL6) expression, which is pivotal for MDSC induction. Blocking IL6 reversed MDSC-associated immunosuppression. Additionally, miR-581, a potential negative regulator of FOXD1, attenuated the impact of FOXD1 on IL6 expression and MDSC differentiation. In vivo experiments demonstrated that tumors derived from FOXD1 OE melanoma cells contained a significantly higher frequency of PD-L1 + MDSC compared with controls, while FOXD1 knockdown resulted in reduced tumor growth and diminished MDSC accumulation.Conclusion Our study elucidated a novel function of FOXD1 in melanoma pathogenesis, highlighting its role in orchestrating the immunosuppressive TME by promoting the generation of MDSC via IL6 upregulation.
Gesehen am 30.06.2025